Transit-Oriented Development in Emerging Cities: A Case Study of Railway Station Areas in Bandung, Indonesia - Saputra, Isro; Hatami , Menanga Puteri; Maharani, Andria (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2025)
Transit-Oriented Development (TOD) is an urban concept that reduces dependence on private vehicles and promotes sustainable mobility. As one of Indonesia's metropolitan cities with a railway serving Bandung and its surrounding areas, Bandung can potentially adopt the TOD concept to address transportation and spatial planning issues. Therefore, this study takes three urban railway station areas as research objects, conducts a detailed evaluation of the comprehensive benefits of land use around these stations, and provides relevant recommendations. This study classifies urban railway transportation stations based on land use functions and establishes a three-tier comprehensive benefit evaluation index system across four dimensions: land use, population and building density, public transportation, and design. The research findings indicate that the  Cikudapateuh stations meet five (5) basic TOD criteria, such as adequate pedestrian lane, mixed-use development, operational public transport service, public transport integration, and building coverage ratio (BCR). These findings indicate that TOD-based development in Cikudapateuh should be prioritized over the other two stations because it better meets the TOD criteria. The policy implications of this study recommend the need for synergy between spatial planning, strengthening transit infrastructure, and stakeholder participation to optimize TOD implementation, thereby achieving sustainable mobility in the future.